Comprehensive analysis of cuproptosis-related genes in immune infiltration and diagnosis in ulcerative colitis - Huang, Jinke; Zhang, Jiaqi; Wang, Fengyun; Zhang, Beihua; Tang, Xudong (Frontiers in Immunology, 2022)
Objectives: Cuproptosis is a recently discovered form of programmed cell death; however, its role in ulcerative colitis (UC) remains a void. Methods: Three gene expression profiles were acquired from the GEO database. Subsequently, the single sample gene set enrichment analysis (ssGSEA) was performed to identify the immune infiltration characteristics of UC. Correlation analysis between cuproptosis and immune infiltration was further conducted, and the cuproptosis-related genes were applied to construct a UC diagnostic model. Subsequently, analysis results of microarray data were experimentally validated by DSS-induced colitis in mice. Finally, therapeutic agents for the cuproptosis-related genes were screened owing to the gaping field of therapeutic agents on cuproptosis. Results: Three gene expression profiles with 343 samples (290 UC and 53 healthy samples) were included. Immune infiltration revealed that UC patients had a higher level of DCs, B cells, CD8+ T cells, iDCs, Macrophages, neutrophils, pDCs, T helper cells, Tfh, Th1 cells, Th2 cells, TIL and Treg than normal subjects. Moreover, almost all cuproptosis-related genes were significantly negatively associated with immune infiltration in UC patients. The risk prediction model based on cuproptosis-related genes showed an excellent discrimination for UC. Animal experiments revealed significant alterations in genes essential for cuproptosis between DSS-induced colitis mice and healthy controls, providing experimental validation for the analysis results of microarray data. Further analysis revealed that Latamoxef, Vitinoin, clomipramine, chlorzoxazone, glibenclamide, Pyruvic acid, clindamycin, medrysone, Caspan, and flavin adenine dinucleotide might be the target agents for cuproptosis-related genes. Conclusions: In conclusion, cuproptosis was significantly associated with immune infiltration in UC, and the cuproptosis-related genes showed an excellent discrimination for UC. Therefore, cuproptosis may be a therapeutic target for UC, and the model based on cuproptosis-related genes facilitates the early diagnosis of UC.